You were never really here [videorecording (DVD)] - Ames, Jonathan; Ramsay, Lynne, 1969-; Phoenix, Joaquin; Roberts, Judith Anna; Samsonov, Ekaterina, 2003- (Lions Gate Entertainment, 2018)
A traumatized veteran, unafraid of violence, tracks down missing girls for a living. When a job spins out of control, Joe's nightmares overtake him as a conspiracy is uncovered leading to what may be his death trip or his awakening.